Holy Bible. [compact disc, unabridged] Historical books of the Old Testament, part 5. - Davidson, Richard M., 1940-; Garrett, Jack; Toren, Suzanne (Recorded Books, LLC, 2004)
Word-for-word unabridged recording of Ezra, Nehemiah, and Esther, narrated in contemporary language for easy understanding.